Pengaruh Kualitas Pelayanan, Inovasi Produk, Dan Online Customer Review Terhadap Kepuasan Pelanggan Di Restoran Joon Canggu - Angelina Putu Debby Maharani; Saortua Marbun; Laras Oktaviani (Journal Research of Management, 2025)
This study aims to determine the effect of service quality, product innovation and online customer reviews on customer satisfaction. The population used those who have visited and returned and are at least 17 years old, is important for Joon Canggu Restaurant, with a sample of 100 respondents. The data analysis techniques used are Descriptive Statistical Analysis, Data Instrument Test, Classical Assumptions, Multiple Linear Regression, t, and Beta Coefficient. Based on the results of the study, it was found that service quality has a positive and significant effect on customer satisfaction, product innovation has a positive and significant effect on customer satisfaction, online customer reviews have a positive and significant effect on customer satisfaction, service quality, product innovation, online customer reviews have a positive and significant effect on customer satisfaction, and product innovation variables have a more dominant effect on customer satisfaction. The suggestions that can be given by the researcher are that Joon Canggu Restaurant is expected increase the speed in providing services, always apply cleanliness standards in the entire processing process properly, always try to make consumers feel satisfied.